If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 9x = 63 + x Solving 7 + 9x = 63 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 9x + -1x = 63 + x + -1x Combine like terms: 9x + -1x = 8x 7 + 8x = 63 + x + -1x Combine like terms: x + -1x = 0 7 + 8x = 63 + 0 7 + 8x = 63 Add '-7' to each side of the equation. 7 + -7 + 8x = 63 + -7 Combine like terms: 7 + -7 = 0 0 + 8x = 63 + -7 8x = 63 + -7 Combine like terms: 63 + -7 = 56 8x = 56 Divide each side by '8'. x = 7 Simplifying x = 7
| 8t+7(7+3t)4+2t= | | 4x+30=11x-40 | | 11-7x=176-42x | | 4t+9+(2t+7)6= | | 7(3x-15)=4(5-x) | | 8x+7=4x+37 | | 6t+3(2+9t)+7= | | 10+2(10)= | | 3(2x-6)=6(1-x) | | 3x-2+x=10-2x | | 5(x+2)=4(9-2x) | | 3+5(5t+1)+8t= | | 4*a-2*1+11=6*a-13 | | 2(x+4)=3(6-x) | | 9*w-2*w+8=4*w+38 | | 3-6x=7-7x | | 7(x+4)=5(x-3) | | 2*m+6=2*m-1 | | (4m+3)9+6m= | | 6*n+21=4*n+57 | | 2+(6m+3)7= | | 6(x+1)=4(x-2) | | 9+9(5+4m)= | | 7(3x+3)=4(4x-1) | | 4+6(3m+2)= | | q+5=2*q+7 | | 3(4x+2)=2(5x-2) | | 4*x+11=x+2 | | 2(2x+3)=3(x+1) | | 6m+7(7m+9)= | | 3x-3=9-x | | 14*k+16*k+88=163 |